2020
DOI: 10.1111/jpy.13063
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Proteome of Lipid Droplets Isolated from the Pennate Diatom Phaeodactylum tricornutum (Bacillariophyceae) Strain pt4 provides mechanistic insights into complex intracellular coordination during nitrogen deprivation

Abstract: Lipid droplets (LDs) are an organelle conserved amongst all eukaryotes, consisting of a neutral lipid core surrounded by a polar lipid monolayer. Many species of microalgae accumulate LDs in response to stress conditions, such as nitrogen starvation. Here, we report the isolation and proteomic profiling of LD proteins from the model oleaginous pennate diatom Phaeodactylum tricornutum, strain Pt4 (UTEX 646). We also provide a quantitative description of LD morphological ontogeny, and fatty acid content. Novel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 183 publications
(367 reference statements)
5
23
0
Order By: Relevance
“…In the study performed by Lupette et al (2019) on mature LDs (7 days of nitrogen starvation), StLDP and PtLDP1 were both recorded in the LD proteome, although no major LD protein was pointed out. The presence of StLDP was further confirmed in a more recent analysis of LD proteome in the Pt4 ecotype of P. tricornutum (Leyland et al, 2020b).…”
Section: Identification Of Major Structural Lipid Droplet Proteinssupporting
confidence: 54%
See 3 more Smart Citations
“…In the study performed by Lupette et al (2019) on mature LDs (7 days of nitrogen starvation), StLDP and PtLDP1 were both recorded in the LD proteome, although no major LD protein was pointed out. The presence of StLDP was further confirmed in a more recent analysis of LD proteome in the Pt4 ecotype of P. tricornutum (Leyland et al, 2020b).…”
Section: Identification Of Major Structural Lipid Droplet Proteinssupporting
confidence: 54%
“…SLC25A4 (an adenine nucleotide translocator) is located in the inner mitochondrial envelope membrane, supporting a possible connection of the LD with the mitochondrion (Lupette et al, 2019). Some of these protein components were confirmed in a more recent proteomic study of LD purified from the Pt4 ecotype of P. tricornutum (Leyland et al, 2020b).…”
Section: Mining Phaeodactylum Tricornutum Lipid Droplet Protein Equipmentmentioning
confidence: 71%
See 2 more Smart Citations
“…This result is in line with the observations of Wong and Franz (2013) who found that Pt4 LDs ranged from 0.1 to 38 µm 3 in N-deficient conditions. Our results also tend to confirm what suggested Jaussaud et al (2020) and Leyland et al (2020) using epifluorescence microscopy. Indeed, Leyland et al (2020) observed a higher yield of LDs from cells disrupted by hypotonic shock in Pt4 compared to Pt1 with multiple small LDs for Pt1 and two relatively large LDs for Pt4.…”
Section: Phenotypic Divergence Between Phaeodactylum Tricornutum Ecotypes and Strainssupporting
confidence: 87%